Dual Antiplatelet Therapy in Patients With Minor Stroke Receiving Intravenous Thrombolysis - Xu, Zhaohan; Chen, Nihong; Sun, Huiling; Jiang, Teng; Deng, Qiwen; Zhou, Junshan; Zhang, Yingdong (Frontiers in Neurology, 2022)
Introduction Concern over the potential severe bleeding risk of dual antiplatelet therapy for minor stroke patients after intravenous thrombolysis leads to different antiplatelet strategies in the secondary prevention of stroke. Our aim was to investigate the effect of dual antiplatelet therapy on patients with minor ischemic stroke receiving intravenous thrombolysis. Methods From November 2016 to April 2021, a total of 855 consecutive patients who received intravenous thrombolysis were observed. We collected and analysed demographic characteristics, medical history, clinical information and important time metrics of patients with minor ischemic stroke. Comparative and multivariate logistic regression analyses were used to explore the clinical significance of single or dual antiplatelet therapy after intravenous thrombolysis. Propensity score matching analyses (1:1 matching including patients’ baseline characteristics) was also performed. Results A total of 245 patients were enrolled in the study (118 patients in the single antiplatelet therapy group and 127 patients in the dual antiplatelet group). No significant difference was found in baseline characteristics except stroke aetiology (p<0.001) for minor stroke patients. The dual antiplatelet group showed a higher proportion of 90-day mRS (0-1) than the single antiplatelet group (p=0.030). Furthermore, patients receiving dual antiplatelet therapy had excellent outcomes (90-day mRS 0-1) after adjustment (odds ratio 2.76, 95% confidence interval 1.27-6.01, p=0.010). Other secondary outcomes (recurrent stroke within 90 days, symptomatic intracerebral haemorrhage and early neurological deterioration) were not significantly different between the two groups. These findings were generally consistent in propensity score analyses. Conclusions Dual antiplatelet therapy may be a potential therapeutic approach in minor stroke patients receiving intravenous thrombolysis. Further randomized controlled trials are required to confirm this finding.